Multilayer scaffold material as well as preparation method and application thereof

Through the design of multi-layer scaffold material, electrospinning and cross-linking technology, the problems of unsatisfactory degradation cycle control of existing anti-adhesion materials and inflammation caused by degradation products are solved, and effective prevention of postoperative adhesions in the environment of wound bleeding and The effect of degradation products without side effects.

CN119158091APending Publication Date: 2024-12-20BEIJING UNIV OF CHEM TECH +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411297107.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing anti-adhesion materials have defects in the control of degradation cycles, and the degradation products may trigger an inflammatory response, which cannot effectively prevent adhesions in wound bleeding environments.

Method used

Using multi-layer scaffolding material, composed of an intermediate fiber membrane and an upper and lower porous sponge, prepared by electrospinning and crosslinking technology, using polyvinyl alcohol, chitosan, hyaluronic acid, sodium alginate and carboxymethylcellulose The same-component controls the degradation period and cross-linking degree of the material, and forms a three-dimensional network structure to enhance water resistance and hemostatic function.

Benefits of technology

A multi-layer anti-adhesion scaffold that maintains mechanical properties and shape for a long time in a bodily fluid environment can effectively prevent postoperative adhesions, no side effects of degradation products, reduced fibrin deposition, high material stability, and continuous function.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a multilayer scaffold material and a preparation method and application thereof, and solves the technical problems that the degradation period of the existing material is unsatisfactory to control, and the degradation product generates side effects, the multilayer scaffold material is composed of a multilayer structure, and comprises a middle layer fiber membrane and porous sponges on two sides, the thickness of the fiber membrane is 200-400 [mu] m, and the thickness of the porous sponges is 500-700 [mu] m. The medical anti-adhesion stent can be widely applied to medical anti-adhesion stents.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biomedical materials, and in particular to a multilayer stent material and a preparation method and application thereof. Background Art

[0002] Postoperative tissue adhesion is the most common problem in surgical treatment of the peritoneum, pericardium, uterus, dural sac and tendons. It not only causes serious postoperative complications, but also greatly increases the difficulty of secondary surgery. Therefore, it is very important to prevent postoperative tissue adhesion. The use of anti-adhesion barriers is a common method and the most effective method in clinical practice. Before suturing the wound during clinical surgery, the doctor will place an anti-adhesion membrane with a physical barrier effect between the operated tissues or organs to prevent postoperative tissue adhesion.

[0003] There are many types of anti-adhesion materials on the market. Although they all have good anti-adhesion effects, the products all have certain shortcomings and cannot meet the requirements of preventing tissue adhesion after cardiac surgery. In general, the products on the market can be divided into two categories according to the degradability of the materials, one is non-degradable anti-adhesion materials, and the other is degradable anti-adhesion materials. Currently, expanded polytetrafluoroethylene (ePTFE) is commonly used in clinical practice, which is a non-degradable anti-adhesion material. It has a good anti-adhesion effect and greatly reduces the difficulty and risk of secondary surgery. However, since it is non-degradable, long-term residence may cause inflammatory reactions and fibrin deposition, and severe fibrosis of surrounding tissues. Oxidized regenerated cellulose (ORC) and hyaluronic acid-carboxymethyl cellulose (HA-CMC) are degradable anti-adhesion materials and also have good anti-adhesion effects, but oxidized regenerated cellulose cannot play a good anti-adhesion role in a bleeding environment, and the hyaluronic acid-carboxymethyl cellulose membrane has poor flexibility, poor operability, and is expensive.

[0004] Injuries are unavoidable during surgery, and bleeding is almost inevitable. The presence of blood will affect the deposition of fibrin, increase the degree of adhesion, and affect the effect of anti-adhesion materials. An ideal anti-adhesion physical barrier requires that the material not only has good biocompatibility, but also can be gradually degraded after the wound heals.

[0005] Chinese patent application with publication number CN111558092A discloses the preparation of a bio-based degradable stent medical membrane, the raw material of which is polyhydroxybutyrate, the material source is single, and the method of controlling the degradation cycle according to the molecular weight has certain limitations.

[0006] A Chinese patent application with publication number CN105396181A discloses a method for preparing a degradable stent medical membrane. However, the material is only polylactic acid, and the method of controlling the degradation cycle according to the molecular weight has certain limitations. In addition, the degradation product is acidic and may cause inflammation. Summary of the invention

[0007] In order to solve the technical problems that the degradation cycle of existing materials is not ideally controlled and the degradation products produce side effects, the present invention provides a multilayer stent material with effectively controlled degradation cycle and degradation products without side effects, as well as a preparation method and application thereof.

[0008] To this end, the present invention provides a multilayer scaffold material, which is composed of a multilayer structure, including a middle layer fiber membrane and porous sponges on both sides, the fiber membrane has a thickness of 200-400 μm, and the porous sponges have a thickness of 500-700 μm.

[0009] Preferably, the fiber membrane components include polyvinyl alcohol and one of chitosan, hyaluronic acid, sodium alginate and carboxymethyl cellulose.

[0010] Preferably, the porous sponge comprises one of sodium alginate, carboxymethyl cellulose, sodium carboxymethyl starch and collagen.

[0011] The present invention also provides a method for preparing a multilayer stent material, which comprises the following steps:

[0012] (1) Preparing a fiber membrane: mixing a polyvinyl alcohol solution with a chitosan solution, a hyaluronic acid solution, a sodium alginate solution or a carboxymethyl cellulose solution, and then adding one of ethylene glycol, succinic acid, citric acid and glutaraldehyde, stirring thoroughly and letting stand to obtain a mixed solution; preparing a fiber membrane by electrospinning the mixed solution, and then drying the obtained fiber membrane in a vacuum drying oven to obtain a fiber membrane; generally, the process parameters of electrospinning are adjusted according to the concentration and viscosity of the spinning solution. The preferred voltage of the present invention is 12 to 16 kV, the spinning speed is 0.6 to 1.0 mL / h, and the receiving distance is 12 cm to 16 cm. (2) Preparing a mixed solution: fully mixing one or two of a sodium alginate solution, a carboxymethyl cellulose solution, a sodium carboxymethyl starch solution and a collagen solution, then adding a crosslinking agent, stirring and crosslinking to obtain a mixed solution; (3) Preparing a multilayer scaffold: pouring part of the mixed solution prepared in step (2) into a mold, then placing the fiber membrane obtained in step (1) in the mold, and then pouring part of the mixed solution into the mold so that the fiber membrane obtained in step (1) is in the middle position, freeze-drying the composite, and the upper and lower layers of the fiber membrane gradually become porous sponges, and finally obtaining a multilayer scaffold material.

[0013] Chitosan is a high molecular weight polysaccharide obtained by deacetylation of chitin, and has good biocompatibility. Sodium hyaluronate is an acidic mucopolysaccharide that exhibits a variety of important physiological functions in the body, such as lubricating joints, regulating proteins, and promoting wound healing. Sodium alginate is a natural polysaccharide carbohydrate, non-toxic, soluble in water to form a viscous liquid, and can be used as a thickener. Carboxymethyl cellulose is a derivative of cellulose after carboxymethylation, and its aqueous solution has the functions of thickening, film formation, and moisture retention. Preferably, the alcoholysis degree of the polyvinyl alcohol is 70% to 99%, and the degree of polymerization is 1000 to 2500; the molecular weight of the chitosan is 50,000 to 250,000; the molecular weight of the hyaluronic acid is 100,000 to 2,500,000; the viscosity of the sodium alginate is 2cp to 5000cp; the molecular weight of the sodium carboxymethyl starch is 90,000 to 200,000; the type of the collagen is type I or type II.

[0014] Preferably, the mass concentration of the polyvinyl alcohol is 4% to 7.5%, the mass concentration of the chitosan is 0% to 1.5%, the mass concentration of the hyaluronic acid is 0% to 1.5%, the mass concentration of the sodium alginate is 0% to 2%, the mass concentration of the carboxymethyl cellulose is 0% to 2%, and the ratio of the mass of the cross-linking agent to the mass of the mixed solution is (1 to 3): (100 to 200).

[0015] Preferably, the cross-linking agent is one of magnesium chloride and calcium chloride.

[0016] The invention also provides an application of the multi-layer stent material as a medical anti-adhesion stent.

[0017] Beneficial effects of the present invention:

[0018] (1) In order to enhance the water resistance of the anti-adhesion stent, especially to maintain good mechanical properties and appearance for a long time in a body fluid environment, the present invention requires that polyvinyl alcohol, chitosan, etc. be formed into a film by electrospinning and then chemically cross-linked by a cross-linking agent at a certain temperature to form a three-dimensional network structure. The degradation cycle of the multilayer medical anti-adhesion stent in the present invention can be controlled by the degree of cross-linking of the middle layer fiber membrane and the upper and lower layers of sponges, wherein the mass concentration of the polymer and the mass ratio of the cross-linking agent to the mixed solution will affect the degree of cross-linking of the middle layer fiber membrane. The mass concentration of the polymer, the mass concentration of the cross-linking agent, and the mass ratio of the polymer solution to the cross-linking agent solution will all affect the degree of cross-linking of the upper and lower layers of sponges.

[0019] (2) In addition, in order to make the anti-adhesion scaffold have a hemostatic function, the spinning membrane is placed in the middle of the cross-linked gel, and porous sponges are prepared on both sides of the spinning membrane by freeze-drying. The upper and lower layers of the porous sponge structure play a hemostatic role. After hemostasis, the sponge can be quickly degraded, reducing the deposition of fibrin around the wound and effectively preventing postoperative adhesion.

[0020] (3) The present invention utilizes the stability of the intermediate layer fiber membrane to enable the multi-layer anti-adhesion stent to maintain morphological integrity and functional stability for a long period of time in the body, thereby achieving the function of inhibiting postoperative adhesion. DETAILED DESCRIPTION

[0021] The present invention is further described below in conjunction with embodiments so that those skilled in the art can easily implement the present invention.

[0022] Example 1

[0023] Step 1: Dissolve 8 parts of polyvinyl alcohol in 92 parts of deionized water (by mass, the same below) to obtain solution A. Dissolve 2 parts of chitosan in 98 parts of 2% (v / v) acetic acid solution (by mass, the same below) to obtain solution B. Mix solution A and solution B in a ratio of 1:1 to obtain a mixed solution, and mix ethylene glycol with the mixed solution in a mass ratio of 1:100 to obtain a spinning solution. The spinning solution is made into a film by an electrospinning process, placed in a vacuum oven at 50°C for 72 hours, and a fiber membrane with a thickness of 300μm is obtained.

[0024] Step 2: Dissolve 4 parts of sodium alginate in 96 parts of deionized water to obtain solution C. Dissolve 2 parts of magnesium chloride in 98 parts of deionized water to obtain magnesium chloride solution D. Mix solution C and solution D in a ratio of 5:0.1, pour the mixed solution into a mold, place the fiber membrane obtained in step 1 on the surface of the solution, pour the mixed solution into the mold again, make the fiber membrane in the middle of the solution, and freeze it in a freeze dryer for 2 days, and finally freeze-dry it for 5 days to obtain a multilayer medical anti-adhesion scaffold.

[0025] Example 2

[0026] Step 1: Dissolve 15 parts of polyvinyl alcohol in 85 parts of deionized water to obtain solution A. Dissolve 3 parts of chitosan in 97 parts of 2% (v / v) acetic acid solution to obtain chitosan solution B. Mix solution A and solution B in a ratio of 1:1 to obtain a mixed solution, and mix glutaraldehyde with the mixed solution in a mass ratio of 3:200 to obtain a spinning solution. The spinning solution is made into a film by an electrospinning process, placed in a vacuum oven at 60°C for 72 hours, and a fiber membrane with a thickness of 300μm is obtained.

[0027] Step 2: Dissolve 4 parts of carboxymethyl cellulose in 96 parts of deionized water to obtain solution C. Dissolve 5 parts of calcium chloride in 95 parts of deionized water to obtain calcium chloride solution D. Mix solution C and solution D in a ratio of 9:0.5, pour the mixed solution into a mold, place the fiber membrane obtained in step 1 on the surface of the solution, pour the mixed solution into the mold again, make the fiber membrane in the middle of the solution, and freeze it in a freeze dryer for 2 days, and finally freeze-dry it for 5 days to obtain a multilayer medical anti-adhesion scaffold.

[0028] Example 3

[0029] Step 1: Dissolve 10 parts of polyvinyl alcohol in 90 parts of deionized water to obtain solution A. Dissolve 2 parts of sodium alginate in 98 parts of deionized water to obtain solution B. Mix solution A and solution B in a ratio of 1:1 to obtain a mixed solution, and mix succinic acid and the mixed solution in a mass ratio of 3:100 to obtain a spinning solution. The spinning solution is made into a film by an electrospinning process, and placed in a vacuum oven at 60°C for 72 hours to obtain a fiber membrane with a thickness of 400μm.

[0030] Step 2: Dissolve 3 parts of sodium carboxymethyl starch in 97 parts of deionized water to obtain solution C. Dissolve 2 parts of calcium chloride in 98 parts of deionized water to obtain solution D. Mix solution C and solution D in a ratio of 7:0.3, pour the mixed solution into a mold, place the fiber membrane obtained in step 1 on the surface of the solution, pour the mixed solution into the mold again, make the fiber membrane in the middle of the solution, and freeze it in a freeze dryer for 2 days, and finally freeze-dry it for 5 days to obtain a multilayer medical anti-adhesion scaffold.

[0031] Example 4

[0032] Step 1: Dissolve 12 parts of polyvinyl alcohol in 88 parts of deionized water to obtain solution A. Dissolve 3 parts of carboxymethyl cellulose in 97 parts of deionized water to obtain solution B. Mix solution A and solution B in a ratio of 1:1 to obtain a mixed solution, and mix citric acid with the mixed solution in a mass ratio of 1:200 to obtain a spinning solution. The spinning solution is made into a film by an electrospinning process, and placed in a vacuum oven at 50°C for 72 hours to obtain a fiber membrane with a thickness of 200 μm.

[0033] Step 2: Dissolve 4 parts of collagen in 96 parts of deionized water to obtain solution C. Dissolve 3 parts of magnesium chloride in 97 parts of deionized water to obtain calcium chloride solution D. Mix solution C and solution D in a ratio of 9:0.1, pour the mixed solution into a mold, place the fiber membrane obtained in step 1 on the surface of the solution, pour the mixed solution into the mold again, make the fiber membrane in the middle of the solution, and freeze it in a freeze dryer for 2 days, and finally freeze-dry it for 5 days to obtain a multilayer medical anti-adhesion scaffold.

[0034] Example 5

[0035] Step 1: Dissolve 12 parts of polyvinyl alcohol in 88 parts of deionized water to obtain solution A. Dissolve 2 parts of hyaluronic acid in 98 parts of deionized water to obtain solution B. Mix solution A and solution B in a ratio of 1:1 to obtain a mixed solution, and mix succinic acid and the mixed solution in a mass ratio of 3:200 to obtain a spinning solution. The spinning solution is made into a film by an electrospinning process, and placed in a vacuum oven at 50°C for 72 hours to obtain a fiber membrane with a thickness of 300μm.

[0036] Step 2: Dissolve 3 parts of sodium carboxymethyl starch in 97 parts of deionized water to obtain solution C. Dissolve 2 parts of calcium chloride in 98 parts of deionized water to obtain solution D. Mix solution C and solution D in a ratio of 5:0.5, pour the mixed solution into a mold, place the fiber membrane obtained in step 1 on the surface of the solution, pour the mixed solution into the mold again, make the fiber membrane in the middle of the solution, and freeze it in a freeze dryer for 2 days, and finally freeze-dry it for 5 days to obtain a multilayer medical anti-adhesion scaffold.

[0037] In the present invention, the mass concentration of the polymer solution and the mass ratio of the crosslinking agent to the mixed solution will affect the degree of crosslinking of the middle layer fiber membrane; the mass concentration of the polymer, the mass concentration of the crosslinking agent, and the mass ratio of the polymer solution to the crosslinking agent solution will affect the degree of crosslinking of the upper and lower sponges. In step 1 of Example 2, if the mass concentration of the polymer is lower and other formula ratios remain unchanged, the degree of crosslinking of the middle layer fiber membrane is higher; if the mass ratio of the crosslinking agent glutaraldehyde to the mixed solution is higher and other formula ratios remain unchanged, the degree of crosslinking of the middle layer fiber membrane is higher. Relative to Example 3, in step 2 of Example 5, the solution crosslinking agent ratio for preparing the porous sponge is higher, and the degree of crosslinking of the upper and lower sponges after freeze drying is higher; at the same time, if the mass concentration of sodium carboxymethyl starch in step 2 of Example 5 is lower and other formula ratios remain unchanged, or the mass concentration of the crosslinking agent calcium chloride is higher and other formula ratios remain unchanged, the degree of crosslinking of the upper and lower sponges after freeze drying is higher.

[0038] The above description is only for the preferred embodiments of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the scope of the claims of the present invention shall be within the scope of protection of the present invention.

Claims

1. A multi-layer scaffold material, Its characteristics are: It is composed of a multi-layer structure, including a middle layer fiber membrane and porous sponges on both sides. The fiber membrane has a thickness of 200-400 μm, and the porous sponges have a thickness of 500-700 μm.

2. The multilayer scaffold material according to claim 1, It is characterized in that The fiber membrane components include polyvinyl alcohol and one of chitosan, hyaluronic acid, sodium alginate and carboxymethyl cellulose.

3. The multilayer scaffold material according to claim 1, It is characterized in that The porous sponge comprises one of sodium alginate, carboxymethyl cellulose, sodium carboxymethyl starch and collagen.

4. The method for preparing the multilayer scaffold material according to claim 1, Its characteristics are: The steps include: (1) Preparing a fiber membrane: mixing a polyvinyl alcohol solution with a chitosan solution, a hyaluronic acid solution, a sodium alginate solution or a carboxymethyl cellulose solution, then adding one of ethylene glycol, succinic acid, citric acid and glutaraldehyde, stirring thoroughly and then standing to obtain a mixed solution; preparing a fiber membrane by electrospinning the mixed solution, and then drying the obtained fiber membrane in a vacuum drying oven to obtain a fiber membrane; (2) preparing a mixed solution: fully mixing one or two of the sodium alginate solution, the carboxymethyl cellulose solution, the sodium carboxymethyl starch solution and the collagen solution, then adding a cross-linking agent, and fully stirring and cross-linking to obtain a mixed solution; (3) Preparing a multilayer scaffold: pouring part of the mixed solution prepared in step (2) into a mold, then placing the fiber membrane obtained in step (1) in the mold, and then pouring part of the mixed solution into the mold so that the fiber membrane obtained in step (1) is in the middle position, freeze-drying the composite, and the upper and lower layers of the fiber membrane gradually become a porous sponge, and finally obtaining a multilayer scaffold material.

5. The method for preparing the multilayer scaffold material according to claim 4, It is characterized in that The alcoholysis degree of the polyvinyl alcohol is 70% to 99%, and the polymerization degree is 1000 to 2500; the molecular weight of the chitosan is 50000 to 250000; the molecular weight of the hyaluronic acid is 100000 to 2500000; the viscosity of the sodium alginate is 2cp to 5000cp; the molecular weight of the sodium carboxymethyl starch is 90000 to 200000; and the type of the collagen is type I or type II.

6. The method for preparing the multilayer scaffold material according to claim 4, It is characterized in that The mass concentration of the polyvinyl alcohol is 4% to 7.5%, the mass concentration of the chitosan is 0% to 1.5%, the mass concentration of the hyaluronic acid is 0% to 1.5%, the mass concentration of the sodium alginate is 0% to 2%, the mass concentration of the carboxymethyl cellulose is 0% to 2%, and the ratio of the mass of the cross-linking agent to the mass of the mixed solution is (1 to 3): (100 to 200).

7. The method for preparing the multilayer scaffold material according to claim 4, It is characterized in that The cross-linking agent is one of magnesium chloride and calcium chloride.

8. Use of the multilayer stent material as claimed in claim 1 as a medical anti-adhesion stent.

Citation Information

Cited By

  • Multilayer hemostatic agent based on sodium alginate and method for its production

    RU2863266C1

  • Multilayer hemostatic agent based on bacterial cellulose and method for its production

    RU2863267C1